Andricus pseudocecconii sp. nova (Hymenoptera: Cynipidae: Cynipini) from Iran - George Melika; James A. Nicholls; Majid Tavakoli; Seyed Ebrahim Sadeghi; Graham N. Stone (نامه انجمن حشره‌شناسی ایران, 2022)
A new species of oak gall wasp, Andricus pseudocecconii Melika, Tavakoli & Stone, sp. nov. (Hymenoptera: Cynipidae, Cynipini) is described. Descriptions, diagnoses, biology, and host associations for the new species are given. The new taxon is supported by morphological and molecular data.